Rapid review microbiology and immunology - Rosenthal, Ken S.; Tan, Michael J. (Philadelphia, PA : Mosby/Elsevier, 2011)
Features photographs, tables and figures that address the microbiology and immunology information you need to know for the USMLE.
Rev. ed. of: Microbiology and immunology / Ken S. Rosenthal, James S. Tan. 2nd ed. c2007. Includes index
NUR
Keywords: Medical microbiology -- Outlines, syllabi, etc; Medical microbiology -- Examinations, questions, etc; Immunology -- Outlines, syllabi, etc; Immunology -- Examinations, questions, etc; Physicians -- Licenses -- United States -- Examinations -- Study guides; Viruses -- Examination Questions; Bacteria -- Examination Question; Communicable diseases -- Immunology -- Examination questions